Estado e desenvolvimento rural - César Nunes de Castro; Caroline Nascimento Pereira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– For many years the discussion about rural development in Brazil was left on the sidelines. The Green Revolution in the 1960s and 1970s, and the increased use of technology sparked an incipient and localized debate on regional and rural development. In the 1980s the discussion lost strength due to State fiscal issues, resuming in the following decade, when the debate on rural development and the pluriative character of rural space gained shape in Brazilian national politics. Other ways of looking at the rural world emerged, no longer strictly attached to the idea of rural space as primarily, or uniquely, destined for agricultural production, which meant giving voice to hitherto marginalized groups. In any case, what is evident throughout the text is the state's participation in Brazilian rural development, by creating the main mechanisms of induction and intervention of agents.
Keywords: O1; O18; 330; rural development; public policy; State